Low complexity bit-parallel multipliers for a class of finite fields - Huapeng Wu; Hasan, M.A. (IEEE transactions on computers, 1998)
New implementations of bit-parallel multipliers for a class of finite fields are proposed. The class of finite fields is constructed with irreducible AOPs (all one polynomials) and ESPs (equally spaced polynomials). The size and time complexities of our proposed multipliers are lower than or equal to those of the previously proposed multipliers of the same class.